Teaching English to muslim students : some pedagogical implications - Othman, Khairiah; Mohd. Asraf, Ratnawati (2008)
Realizing the importance of education in shaping future generation, Muslim scholars (al-Attas,(1993); al-Faruqi ,1986) have advocated Islamic values to be inculcated in every discipline. English language teaching is no exception as it is not neutral, but in fact, has been infused with the values of the West, as reflected in Western instructional materials zar,1993;Alptekin,1993;Pennycook,1994;Elnimeiri,1996;Ratnawati,1997). This is inevitable as language is a carrier of culture (Corder, 1973) and therefore language and culture are intertwined and inseparable (Lado, 1956; Alptekin, 1993). A study was conducted to find out how Muslim teachers inculcated Islamic values in the teaching of English. The methodology adopted were interview and classroom observation. The study found five recurring themes employed by these teachers in teaching English to Muslim students. The teachers highlighted un-Islamic practices, brought in Islamic concepts and Islamic Arabic terms, related the texts to the stories of the prophets, with special reference to Prophet Muhammad, discussed current issues pertaining to Muslims and finally made references to Quranic verses and hadith.